2020
DOI: 10.1016/j.jcte.2020.100230
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of gender affirming hormone therapy on body mass index in transgender individuals: A longitudinal cohort study

Abstract: Introduction Many transgender people take hormone therapy to affirm their gender identity. One potential long-term consequence of gender affirming hormone therapy is increased body mass index (BMI), which may be associated with metabolic syndrome, cardiovascular disease and higher mortality. Only a few published studies explored changes in BMI in transgender people taking gender affirming hormone therapy (GAHT). Objective To examine the changes in BMI longitudinally in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Regardless, the captured adipose nuclei express the androgen receptor as expected and are thus of interest, especially considering the documented impact of androgens on energy metabolism and the fact that transgender men experience weight loss and redistribution of body fat (Fig. S2E, S12B) 13,[75][76][77][78] .…”
Section: Androgen Treatment Elicits Lipid Reduction Through Epithelia...mentioning
confidence: 69%
“…Regardless, the captured adipose nuclei express the androgen receptor as expected and are thus of interest, especially considering the documented impact of androgens on energy metabolism and the fact that transgender men experience weight loss and redistribution of body fat (Fig. S2E, S12B) 13,[75][76][77][78] .…”
Section: Androgen Treatment Elicits Lipid Reduction Through Epithelia...mentioning
confidence: 69%
“…Building upon evidence that estrogen replacement therapy in transgender females is protective against metabolic syndrome [ 12 , 13 ], we aimed to investigate whether central estrogen supplementation in males would influence metabolic syndrome phenotypes. To evaluate this, obese male mice were instrumented with ICV cannulas and received daily 6-day administration [ 24 , 28 ] of low-dose central 17-β-estradiol administration ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods oversimplify the role of sex hormones in metabolic homeostasis as they often investigate the dominant sex hormone with little evaluation of alternate sex hormone signaling (e.g., either testosterone in women or estrogen in men). Interestingly, transgender individuals receiving feminizing gender affirming therapy (i.e., estrogen) appear to be relatively protected from metabolic syndrome conditions, including type II diabetes, insulin resistance, and cardiovascular dysfunction [ 12 , 13 ]. However, global estrogen replacement poses numerous hurdles.…”
Section: Introductionmentioning
confidence: 99%
“…The patients in this study with elevated BMI did not have surgery. Multiple cohort studies of trans adolescents and adults demonstrate a high prevalence of increased BMI overall [52][53][54] . A 2017 NIH analysis of Behavioral Risk Factors Surveillance System data showed that 72.4% of the trans adult respondents have a BMI equal to or greater than 25 kg/m 2 , compared to 65.5% of cisgender respondents [21] .…”
Section: Published Literature Does Not Provide Robust Evidence For Fa...mentioning
confidence: 99%